The multibeam linear ion accelerator: calculation and experiment - Gavrilov, N.M.; Gavrilov, M.K.; Bogatchenkov, D.A.; Ivanov, Е.V.; Komarov, D.A.; Strukov, J.N. (Вопросы атомной науки и техники, 2004)
The accelerating structure consisting of cylindrical screen with electrodes of coil types radialy disposed, which
the current-conductive annuluses with tubes of driftage disposed azimuth of annulus are attached has been
suggested. By way computer simulation were received the base-frequency of structure, shunt-impedance,
distribution of field in the accelerating gaps. The experimental researched of frequencies generation coil in screen
and field distribution functions were made. Пропонується прискорююча структура, що складається з циліндричного екрану з радіально
розташованими електродами спірального типу, до яких кріпляться струмопровідні кільця з трубками
дрейфу, розташованими по азимуту кільця. Шляхом чисельного моделювання були отримані робоча
частота, шунтовий імпеданс, розподіл полів в прискорюючих зазорах. Проведено експериментальні
дослідження частот збудження спіралі в екрані і розподілу полів. Предлагается ускоряющая структура, состоящая из цилиндрического экрана с радиально
расположенными электродами спирального типа, к которым крепятся токопроводящие кольца с трубками
дрейфа, расположенными по азимуту кольца. Путем численного моделирования были получены рабочая
частота, шунтовой импеданс, распределение поля в ускоряющих зазорах. Проведены экспериментальныеисследования частот возбуждения спирали в экране и распределения поля.